Indoor Air Quality in Portuguese Day Care Centers - ENVIRH Project - Cano, Manuela (2012)
This paper describes field measurements of indoor air quality (IAQ) parameters, performed in 19 Portuguese Children Day Care Centers (CDCC) during the springtime of 2011 and aims to characterize the indoor environment. The results demonstrate an association between carbon dioxide and bacterial concentrations, which in turn are affected by the number of children present in each classroom. Indoor PM10 concentrations were higher than outdoor levels (I/O ratio>1) and was also found statistically significant association between PM10 concentrations and the type of floor covering materials. These results provide evidence that IAQ is inadequate and, as a consequence, human source contaminants such as bacteria and carbon dioxide accumulate indoors. This study suggests that it is necessary to improve ventilation in order to achieve a healthier indoor environment.